EFFORTS TO IMPROVE READING ABILITY THROUGH LETTER CARD GAMES IN CHILDREN AGED 5-6 YEARS - Jamilah, Ayu Fajarwati, Afifah (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
Jasturi, 2024 was motivated by the problem of reading ability in Kober Anugrah, Binuang District, Serang Regency which was still not optimal. So the researcher wanted to improve reading ability by creating a thesis title